Does the Schema of Top Peer Pressure and Its Relationship with Achievement Change from Junior High School to University? - Khodadady, Ebrahim; Moghaddam, Hassan (Innovare Journal of Education, 2023)
This study aimed to find out what cognitive taxa constitute the schema of Top Peer Pressure (TPP) among Junior High School Students (JHSSs), which taxa associated with the JHSSs’ English and school achievement and whether JHSSs’ taxa differ from those of Undergraduate University Students (UUSs). To this end the TPPS was administered to 304 HSSs and their responses were subjected to Principal Axis Factoring and Varimax with Kaiser Normalization. The results showed that six factors representing JHSSs’ cognitive taxa of kingdom, phylum, class, order, family and genus underlie the TPPS. Among them, the taxon of the kingdom was associated significantly with both English language and school achievement, while only the taxon of the family was associated significantly with English language achievement. Contrastive analysis of JHSSs’ cognitive taxa with those of UUSs showed that the UUSs pathologically manipulate the items comprising the schema of TPP not only at its kingdom taxon but also at the taxa of phylum, class and order to justify their low university achievement. The results are discussed and suggestions are made for future research.